Evaluation of the GCS-Pupils Score for PrOgnosis in trauMatic brAin injury- The COMA Study - Mahajan, Charu; Sengupta, Deep; Kapoor, Indu; Prabhakar, Hemanshu; Kumar, Vijay; Purohit, Shobha; Priya, Vansh; Srivastava, Shashi; Thakur, Deepali; Karnik, Hemangi; Sati, Hem Chandra; Kalaivani, Mani (Brain injury, 2023)
Glasgow Coma Scale-Pupils (GCS-P) score has been found to be strongly related to in-hospital mortality in retrospective studies. We hypothesized that GCS-P would be better prognosticator than Glasgow Coma Scale (GCS) in patients with traumatic brain injury (TBI). In this prospective, multicentric, observational study, GCS and GCS-P scores were noted in adult TBI patients at ICU admission. Demographic variables, relevant clinical history, clinical/radiological findings and ICU complications were also noted. Extended Glasgow Outcome scale was noted at hospital discharge and at 6 months post-injury. Logistic regression analysis was carried out to estimate the odds for poor outcome adjusted for covariates. Sensitivity, specificity, area under curve (AUC) and odds ratio are reported for poor outcome at estimated cutoff point. A total of 573 patients were included in this study. The predictive power for mortality, shown by the AUC, was 0.81 [95% CI: 0.77-0.85] for GCS and 0.81 [95% CI: 0.77-0.86] for GCS-P score, both being comparable. Similarly, the predictive ability for outcome at discharge and 6 months, the AUC-ROC for both GCS and GCS-P were comparable. GCS-P is a good predictor of mortality and poor outcome. However, the predictive performance of GCS and GCS-P for in-hospital mortality and functional outcome at discharge and at 6 months remains comparable.